Spontaneous defervescence and its prediction in the acute phase of Kawasaki disease - Shin, Eun Jung; Yu, Jeong Jin; Shin, Hyewon; Kwon, Hyuck Jin; Kim, Jin Ho; Kim, Mi Jin; Cha, Seulgi; Baek, Jae Suk (Frontiers in Pediatrics, 2022)
Background In Kawasaki disease (KD), fever occasionally resolves spontaneously before 10 days from the onset, right after diagnosing. However, there is not enough evidence of intravenous immunoglobulin (IVIG) treatment in this case. The aim of this study was to investigate the relationship between spontaneous defervescence and coronary artery aneurysm and to develop a scoring model for its prediction in acute KD. Methods All patients admitted for acute KD in Asan Medical Center were considered for inclusion. Acute management involved the administration of 2 g/kg of IVIG and 5 mg/kg/day of aspirin. The patient whose temperature was <37.5°C for more than 48 h from the diagnosis was discharged under the judgment of spontaneous defervescence, without IVIG administration. Results The incidence of coronary artery aneurysm was 5.7% in 94 defervesced patients and 4.6% in the 1,277 patients treated with IVIG in the subacute phase (P = 0.593), and 2.5 and 2.2% in respective patient groups in the convalescent phase (P = 0.924). A scoring model which predicted spontaneous defervescence under the combination of C-reactive protein ≤10mg/dL and ≥2 conditions of no rash, neutrophil ≤65%, and/or alanine aminotransferase ≤80 IU/L, was developed and showed 80.7% sensitivity, 68.8% specificity, 15.8% positive predictive value, and a 97.8% negative predictive value. Conclusion The incidence of coronary artery aneurysm in patients with the defervesced KD was not different from the IVIG treated patients. In the cases suitable for the predictive model, patients can wait for the spontaneous defervescence under intensive observation by medical professionals.